2019
DOI: 10.1530/ec-18-0370
|View full text |Cite
|
Sign up to set email alerts
|

Association of single-nucleotide polymorphisms in the IL27 gene with autoimmune thyroid diseases

Abstract: Background Accumulating data have shown that interleukin-27 (IL27) polymorphisms are linked to the susceptibility of some autoimmune diseases. We assessed whether there was an association between three single-nucleotide polymorphisms (SNPs) of IL27 gene and autoimmune thyroid diseases (AITDs). Methods Three SNPs (rs153109, rs17855750 and rs181206) of IL27 gene were genotyped by Hi-SNP high-throughput genotyping in 843 patients with AITDs (516 Graves’ disease (GD) and 327 Hashimoto’s thyroiditis (HT)) and 677 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…IL-27 most likely enhances Th1 lymphocyte function and suppresses Th2, which would suggest an immune imbalance similar to that seen in T1DM or HD [49]. In line with this assumption, studies of single nucleotide polymorphisms have confirmed an association between IL-27 [50] and the SIRT1 gene with autoimmune thyroid diseases [51]. In this study, aTG was positively correlated with the IL-27 serum levels in women with T1DM, but not significantly with sirtuin 1 serum levels.…”
Section: Discussionsupporting
confidence: 73%
“…IL-27 most likely enhances Th1 lymphocyte function and suppresses Th2, which would suggest an immune imbalance similar to that seen in T1DM or HD [49]. In line with this assumption, studies of single nucleotide polymorphisms have confirmed an association between IL-27 [50] and the SIRT1 gene with autoimmune thyroid diseases [51]. In this study, aTG was positively correlated with the IL-27 serum levels in women with T1DM, but not significantly with sirtuin 1 serum levels.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, the multiple pairings of IL-30 and roles for IL-30 in human immunity may suggest that we do not appreciate the full picture of human IL-30 secretion and functions yet. As an example, polymorphisms in the IL-30 gene have been reported in numerous disease settings, including premature coronary artery disease 100 , bladder cancer 101 , osteosarcoma 102 , asthma 103 , autoimmune thyroid disease 104 , and IBD 105 . Whether these mutations alter the folding and secretion pattern of IL-30 or one of its pairings remains to be determined.…”
Section: Disparities In Il-30 Biology Between Mice and Menmentioning
confidence: 99%
“…Genomic DNA samples were isolated using the QIAamp DNA Blood Mini Kit (Qiagen, Berlin, Germany) 27 and the extracted DNA sample was amplified by polymerase chain reaction (PCR). Hi‐SNP high‐throughput genotyping methods 28 were used to genotype the amplification products (Shanghai Biowing Applied Biotechnology CO. LTD, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%